Virtual learning of the tribal students in Bangladesh: Constrictions and propositions - Quazi Farzana Yesmin; Mohammad Ehsanul Islam Khan (Institute of Advanced Engineering and Science, 2021)
This paper depicts the current panorama of virtual learning of the tribal students in Bangladesh with the constrictions and possible solutions. The study aimed to deal with the major issues about tribal students’ online education by bringing out the key restraints of their distance learning and the possible solutions. The researchers followed a mixed method using a 5-point Likert Scale to point out the learner sensitivities, an online Focus Group Discussion (FGD) to know specific information from all the tribes who participated in the study. Additionally, four different questions were also set for multiple response analyses. The results suggested that the tribal students have not agreeably received adequate facilities such as technological support, university funding, departmental encouragements, or monetary benefits from the quota system in the current pandemic (COVID-19) time to attend virtual learning sessions though they expect arrangements and future steps for academic learning. All institutions also could not provide them adequate opportunities to attend online classes. In conclusion, the study proposed some imperative measures for example, inclusion of flipped classroom, introducing blended learning henceforth, revising quota facilities, adequate electricity support and internet connection, to help the tribal students as they should not get deprived.